IMPLEMENTATION OF GREEN MANAGEMENT IN IMPROVING COMPANY IMAGE AND CONSUMER SATISFACTION - R. Taufiq Nur M; Elida Zia’ul Huda (Adisam Publisher, 2025)
This research is a literature review which aims to analyze the role of green management implementation in improving company image and consumer satisfaction. The method used is a systematic literature study of various scientific sources, including relevant journal articles, books and conference proceedings. The study results show that green management practices, such as efficient waste management, use of renewable energy, and application of sustainability principles in operational processes, contribute positively to the formation of an environmentally friendly and socially responsible company image. A positive company image then influences consumer satisfaction and loyalty, because consumers tend to support companies that are in line with the sustainability values ​​they adhere to. However, this study also found gaps in the literature regarding differences in influence between industries, limitations of long-term studies, and a lack of analysis of mediating and moderating factors in the relationships studied. Therefore, further, more in-depth and contextual research is needed. This study provides theoretical contributions to the development of green management literature as well as practical implications for companies in building reputation and long-term relationships with consumers through sustainability strategies.